Evaluation of the Antidiabetic Activities of the Fruit of (Afzel.) Bullock and Identification of Its Antidiabetic Agent - Marcus D Ayoola; Yetunde B Ogundeko; Temiloluwa D Obanleowo; Deborah O Omole; Blessing N Chukwu; Kolade O Faloye (Bioinformatics and Biology Insights, 2024)
The study investigated the antidiabetic potentials of the fruit extract of Parquetina nigrescens with the aim of justifying its folkloric antidiabetic usage in some part of Nigeria. Acute toxicity test of the plant extract was assessed using Lorke’s method. Its antidiabetic activities were assayed in α-amylase, α-glucosidase, glucose, and streptozotocin-induced diabetic rats’ models at various doses with acarbose and glibenclamide (5 mg/kg) as positive controls. Molecular docking studies were performed to identify the antidiabetic constituent of the extract and elucidate its possible mechanism of action. The estimated median lethal dose (LD 50 ) of the extract was above 5000 mg/kg. In the α-amylase, α-glucosidase study, the extract elicited concentration-dependent activity similar to acarbose. In the glucose-induced hyperglycaemic model, 200 mg/kg of the extract was the most effective dose with comparable ( P  > .05) antihyperglycaemic activity to glibenclamide (5 mg kg) at 1 to 4 h. Also in the streptozotocin-induced diabetic rats model, 100 and 200 mg/kg of the extract gave comparable ( P  > 0.05) activity on days 4 to 14 that were significantly better than that of glibenclamide on days 4 to 7. The n-hexane and ethylacetate fractions of the extract, both at 200 mg/kg were the most active with comparable activity to glibenclamide at all time points. The molecular docking studies identified isorhoifolin as the best binder against alpha amylase with binding energy (−9.1 kcal/mol), alpha glucosidase (−9.4 kcal/mol), sodium-glucose cotransporter-2 (−9.5 kcal/mol), peroxisome proliferator activated receptor gamma (−10.3 kcal/mol), 11β - Hydroxysteroid dehydrogenase (−10.8 kcal/mol), and dipeptidyl peptidase IV (−9.4 kcal/mol). The results of the antidiabetic study of P nigrescence fruit extract justified its usage in ethnomedicne in diabetes management.